Challenges of New Technologies in the Romanian Management - Gheorghe Popovici; Monica Roșu (Robotica & Management, 2018)
The paper presents the results of the study on the challenges of new technologies in the Romanian management starting from the premise that today, no matter how good you are in your business, you must always learn and keep up with the new technologies based on computers, Internet and smart phones to be a good manager. Because no matter how well the business goes today, tomorrow a storm may come, like the unexpected occurrence of the 2008-2013 economic crisis. A first challenge is that a new business must address a new generation - the hypersensitive generation (Z) of young people born after 2000 with traits different from those of generations Y, X, W and V. Another challenge is the integration of the "cloud" technology into the business for a better document management in the "electronic cloud" and information mobility. Every challenge in management can be compared to a sporting competition and to that end the paper forwards a parallel between leadership and competition sports.